Case Report: What Are We Doing for Our "20/20 Unhappy" Scleral Lens Patients?. Issue 9 (September 2020) - Nguyen, Lan Chi; Kauffman, Matthew J.; Hastings, Gareth D.; Applegate, Raymond A.; Marsack, Jason D.
Abstract : SIGNIFICANCE: Scleral lenses (SLs) partially mask higher-order aberrations (HOAs) in highly aberrated eyes. Although visual acuity (VA) may show satisfactory quantitative clinical outcomes during SL wear, residual (uncorrected) HOAs can leave subjective visual quality goals unmet. PURPOSE: The purpose of this study was to report a case where a "20/20 unhappy" patient with SLs was able to meet visual goals with wavefront-guided SLs. CASE REPORT: A 40-year-old male with bilateral keratoconus, whose Snellen VA with SLs was 20/20 +2 right eye (OD) 20/16 +2 left eye (OS), reported halos and glare at night and perceptual smearing. When viewing a point of light, a "Ferris wheel" shadowing was observed OD and a U-shaped shadowing OS. Residual higher-order root mean square wavefront error was 0.49 μm OD and 0.39 μm OS; visual image quality measured by visual Strehl ratio was 0.067 OD and 0.092 OS (pupil size, 4.00 mm). Wavefront-guided SLs reduced residual higher-order root mean square to 0.19 μm OD and 0.25 μm OS, VA improved to 20/10 OD and 20/13 OS, and visual Strehl improved to 0.150 OD and 0.121 OS. The patient reported reduced smearing, shadowing, and night vision concerns, meeting his visual expectations and goals. CONCLUSIONS: Wavefront sensing quantifies both lower and HOAs, which can cause visual dissatisfaction in individuals with highly aberrated eyes, despite sometimes reaching typical levels of VA. As wavefront-guided SLs targeting these residual aberrations to improve visual image quality become more available, they should be considered for 20/20 unhappy patients when conventional clinical options are unsatisfactory.